Research and policy communication efforts by CGIAR Research Program on Wheat scientists directly contributed to a Government of Zimbabwe Climate Smart Agriculture Framework - CGIAR Research Program on Wheat (2019)
The Farm Mechanization and Conservation Agriculture for Sustainable Intensification (FACASI) project contributed to a national climate smart agriculture policy for Zimbabwe - through targeted research and communication on the most effective approach for smallholder farmer adoption of climate smart agricultural practices in eastern and southern Africa.